Implementation of Halal Certification for Segar Doger Poncowati Products - Tommy Saputra; Ulil Albab; Heri Sutopo (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
This research aims to understand the production process at Segar Doger Poncowati. To understand the implementation of halal certification or halal labeling for Segar Doger products in Poncowati. This research employs a qualitative approach with a descriptive method. The types of data used in this research are primary and secondary data. Data collection techniques include observation, interviews, and documentation. The research informants consisted of 1 small and medium-sized enterprise (SME) manager, 1 SME financial personnel, and 2 SME employees. The data analysis techniques involve data reduction, display, and conclusion drawing. Production consists of providing goods and services while considering the values ​​of justice and benefits for society. The research results indicate that Segar Doger's output is based on ingredients such as freshly squeezed orange juice and granulated sugar as the main components. The production equipment is relatively simple and manual. The Halal Certificate held by Segar Doger is issued by the Lampung branch of the Indonesian Council of Ulama (MUI) and is valid for 2 years, requiring renewal every 2 years.